Consumer behavior in fast food restaurants - Kulhavá, Eva (2021)
The goal of this master’s thesis is segment and provide insight on the consumer behavior of fast-food restaurants visitors in Czech Republic. This analysis is conducted to identify consumer segments, which fast food truck Circus Burger should focus on. Analysis and segmentation conducted and was based on both secondary and primary date. The source of secondary data was MML-TGI survey and source of primary data was questionnaire survey (N=254) conducted by the author. Segmentation based on secondary data uncovered five segments, while the segmentation based on primary data uncovered four segments. Subsequently the segments uncovered based on both data sources were synthesized. Two out of five segments were identified as most suitable for Circus Burger to focus on, taking account the market segmentation criteria and selected targeting strategy.